Physical fitness components in primary school children - A comparative study between deaf and hearing children - - mounir talahma,; ادريس محمد صقر جرادات, (sports creativity, 2025)
This study aimed to identify the levels of some physical fitness components in deaf male children and compare them with hearing children. The study consisted of two age groups, 11-13 years and 8-10 years, and each group was further divided into two groups according to disability: deaf and hearing.